2012
DOI: 10.1016/j.optcom.2011.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Pedestal free pulse compression of chirped optical solitons

Abstract: We consider the evolution of nonlinear optical pulses in inhomogeneous optical media wherein the pulse propagation is governed by the nonlinear Schrödinger equation with varying dispersion. We adopt the Painlevé analysis in order to obtain the condition for the soliton pulse propagation. We find that there exist two dispersion profiles satisfying this criterion, namely, the constant dispersion and exponentially dispersion decreasing profiles. In the exponentially varying dispersion media, we explain the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Thus, high degree pulse compression in a short distance is more desirable. It has been demonstrated that chirped high order solitons in a dispersion varying medium is effective in enhancing the compression in short distance [21]. Specifically, when a chirped 2-soliton breather is used, the compression factor can be enhanced by more than 3 times in a same propagation distance [21].…”
Section: Chirped 2-soliton Breather Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, high degree pulse compression in a short distance is more desirable. It has been demonstrated that chirped high order solitons in a dispersion varying medium is effective in enhancing the compression in short distance [21]. Specifically, when a chirped 2-soliton breather is used, the compression factor can be enhanced by more than 3 times in a same propagation distance [21].…”
Section: Chirped 2-soliton Breather Compressionmentioning
confidence: 99%
“…Thus, a high degree pulse compression in a short distance of the waveguide taper is desirable. It has been shown that the compression factor of self-similar compression for the same waveguide length can be enhanced by more than 3 times if 2-soliton breather is used [21]. For 2-soliton breathers, the periodic higher-order soliton evolution accompanies the self-similar compression.…”
Section: Chirped 2-soliton Breather Compression In a Slotmentioning
confidence: 99%
“…(5) in which the nonlinearity is assumed to be constant, i.e. γ(z) = γ(0), has been well studied [21,33,40]. From Eqs.…”
Section: Theoretical Model and Principlementioning
confidence: 99%
“…But adiabatic compression requires long length of fiber [26][27][28][29]. Self-similar compression can avoid the drawbacks in the above two pulse compression schemes and provide pedestal-free pulse compression with high compression factor in a short segment of fiber [30][31][32][33][34]. Selfsimilar compression of chirped solitons in dispersion exponentially decreasing fibers (DEDFs) has been discussed [21,32,33].…”
Section: Introductionmentioning
confidence: 99%
“…But the long fiber length required is undesirable in most systems because of compactness and cost [16][17][18]. Compared with the adiabatic compression, self-similar pulse compression can achieve large compression factor without pedestal generation in much shorter nonlinear media [3,[19][20][21][22][23]. In a 6.4 m nonlinearity increasing photonic crystal fiber (PCF) taper, a 1 ps pulse is self-similarly compressed to 53.6 fs with low pedestal [3].…”
Section: Introductionmentioning
confidence: 99%